Distance learning as an opportunity? - Bulgakova, Elena; Buinov, Alexei; Skvortsov, Mikhail (project baikal, 2020)
The article considers a non-standard design practice in a distance learning format at the Department of Architecture and Design of Moscow Information and Technology University-Moscow Architecture and Construction Institute (MITU-MACI). It also reveals the peculiarities of digitalization as means of modernization and advancement of the learning process.
Keywords: intensive design course; individual educational trajectory; creative activity; digital footprint; comfortable environment; educational digital platform